STRATEGIES IN TEACHING GRAMMAR TO SECONDARY SCHOOL STUDENTS (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Teaching grammar to secondary school students is one of the most essential yet challenging tasks in English language education. This article explores effective strategies for teaching grammar in a way that promotes understanding, retention, and practical application. Drawing on classroom observations, teacher interviews, and student feedback, the study evaluates the impact of explicit, inductive, communicative, and task-based grammar teaching approaches. The findings indicate that combining form-focused instruction with interactive activities and contextualized practice significantly enhances student engagement and grammatical accuracy. The article also provides recommendations for secondary school teachers seeking to make grammar instruction more meaningful and learner-centered.